Electronic cigarette essence sheet based on efficient environment-friendly low-temperature polymer volatilization and manufacturing process thereof
By using a composite material of modified polylactic acid and alumina nanoparticles in electronic cigarette flavor sheets, the problem of poor thermal conductivity of traditional flavor sheets is solved, the uniform volatility and environmental protection of essential oils are achieved, and the user experience and product performance are significantly improved.
Patent Information
- Application Number
- CN202411520665.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-03-07
AI Technical Summary
The thermal conductivity of traditional electronic cigarette flavor tablets is poor, resulting in uneven volatility of essential oils during heating and the material is not environmentally friendly, affecting the user experience and the environment.
The composite material based on polylactic acid is used to improve the thermal stability and thermal conductivity of the material through the composite with alumina nanoparticles, and the ratio of essential oil to polylactic acid is optimized through Flory-Huggins theory, and the fragrance sheet is formed by combining ultrasonic technology and hot pressing.
It significantly improves the thermal conductivity of the flavor sheets, achieves uniform volatility of essential oils under low temperature conditions, extends the service life of the flavor sheets, improves the user experience, and improves the environmental protection of the materials.
Smart Images

Figure CN119563918A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic cigarettes, and in particular to an electronic cigarette flavor sheet based on high-efficiency, environmentally friendly, low-temperature polymer volatilization and a production process thereof. Background Art
[0002] With the popularity of electronic cigarette products, consumers have higher and higher requirements for the user experience of electronic cigarettes, especially in terms of the continuity and uniformity of flavor release and the environmental friendliness of the product. Traditional electronic cigarette flavor tablets usually use paraffin or plastic materials as the matrix. Although these materials can effectively release flavors when used, they have problems such as uneven volatilization, overheating, and negative impact on the environment. Therefore, research on a new type of flavor tablet material that can volatilize evenly under low temperature conditions, is environmentally friendly and stable has become an important topic in the electronic cigarette industry.
[0003] Most of the existing electronic cigarette flavor sheets use non-degradable plastics or synthetic resins as the base material. Although these materials can provide a certain mechanical strength and lasting release of essential oils during use, their thermal conductivity is poor, resulting in uneven volatilization of the essential oils during heating. In addition, since the plastic matrix is not environmentally friendly, these materials impose a heavy burden on the environment after use, especially when a large amount of waste enters the ecosystem, it is difficult to degrade, causing serious environmental problems. At the same time, the solutions used in the prior art to increase the volatilization of flavors often cause the material to produce odors due to local overheating during use, which seriously affects the user experience.
[0004] However, there are still some problems with the material structure and performance of flavor sheets in the prior art, especially poor thermal conductivity leads to uneven volatilization of flavors, which is one of the common problems of electronic cigarette flavor sheets. During use, the flavor sheet may cause local overheating or unstable volatilization rate due to uneven heat distribution, which in turn affects the release effect of the flavor. Especially under low temperature conditions, materials with poor thermal conductivity can hardly ensure that the flavor can volatilize continuously and evenly, which directly affects the user experience. Therefore, there is an urgent need for an improved electronic cigarette flavor sheet that can achieve uniform volatilization of essential oils by improving thermal conductivity and optimizing material structure, while having good environmental protection. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides an electronic cigarette flavor sheet based on high-efficiency, environmentally friendly, low-temperature polymer volatilization and a production process thereof, which solves the problem that traditional electronic cigarette flavor sheets have a long-lasting release of essential oils, but their thermal conductivity is poor, resulting in uneven volatilization of the essential oils during the heating process.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: based on a high-efficiency, environmentally friendly, low-temperature high-molecular-weight volatilization electronic cigarette flavor sheet, the flavor sheet includes:
[0007] The flavor sheet includes a composite material based on polylactic acid, wherein the modification of the polylactic acid includes compounding with aluminum oxide nanoparticles to improve its thermal stability;
[0008] The composite material further includes a certain proportion of essential oil, which is bonded to the polylactic acid through a specific chemical bond and is used to volatilize at a controlled rate and low temperature during heating;
[0009] The volume fraction of aluminum oxide nanoparticles is precisely controlled at 5%, which enhances the thermal conductivity of the composite material and achieves a more uniform heat distribution, thereby optimizing the volatilization performance of the flavor;
[0010] The thermal conductivity of the composite material is calculated according to a modified Maxwell model, which takes into account the shape and distribution heterogeneity of the nanoparticles.
[0011] Preferably, the essential oil is selected from the category of essential oils with a relatively high boiling point and a stable chemical structure to ensure effective volatilization even at low temperatures.
[0012] Preferably, the thermal conductivity optimization of the composite material is performed based on the Maxwell model, and the model formula is as follows, which is used to accurately control the dispersion uniformity and shape factor of the nanoparticles:
[0013]
[0014] where k matrix is the thermal conductivity of polylactic acid, k particle is the thermal conductivity of alumina, and φ is the volume fraction of alumina nanoparticles.
[0015] Preferably, the essential oil is selected from citrus or mint, and the volume ratio of the essential oil to polylactic acid is 2%, which is optimized based on the Flory-Huggins theory to achieve the best volatilization effect and fragrance persistence, and is calculated using the following formula:
[0016]
[0017] Where V 1 is the molar volume of the essential oil, R is the gas constant, T is the absolute temperature, δ 1 and δ 2 are the solubility parameters of essential oils and polylactic acid, respectively.
[0018] The production process of high-efficiency, environmentally friendly, low-temperature polymer volatile electronic cigarette flavor tablets includes the following steps:
[0019] Step 1, mixing the modified polylactic acid and alumina nanoparticles in a predetermined ratio to ensure that the alumina nanoparticles are evenly distributed;
[0020] Step 2, adding the essential oil to the mixture, controlling the adding speed and mixing temperature to maintain the chemical stability of the essential oil;
[0021] Step 3: Using ultrasonic technology to optimize the dispersion of aluminum oxide nanoparticles in the polylactic acid matrix, thereby improving the thermal conductivity and flavor release performance of the final product;
[0022] Step 4: Form the flavor tablets by hot pressing under controlled pressure and temperature to ensure the thermal stability of the material and the uniform volatilization of the flavor.
[0023] Preferably, in step 2, in the step of mixing modified polylactic acid and aluminum oxide nanoparticles, dynamic light scattering technology is used to accurately measure and monitor the average particle size and particle size distribution of the nanoparticles to ensure that the average particle size of the nanoparticles is controlled within the range of 50 to 100 nanometers to achieve a predetermined dispersion uniformity.
[0024] Preferably, in the step of adding essential oil in step 2, an automatic titration system is used to accurately control the amount of essential oil added, and the system automatically adjusts the addition rate of the essential oil based on the Flory-Huggins theory and real-time solubility monitoring results to ensure that the volume ratio of essential oil to polylactic acid is maintained at a constant 2%.
[0025] Preferably, in the step 4, the hot pressing molding process is carried out in a specific device that can accurately control the pressure and temperature, the pressure is set to 200 psi, the temperature is set to 65° C., and the pressing time is fixed to 10 minutes. During the melt blending process in the step 1, a high-speed agitator is used to improve the dispersion uniformity of the nanoparticles to ensure that the flavor sheet has good thermal conductivity.
[0026] Preferably, in the step 2, the pressure range of the vacuum extraction process is controlled to be 0.01 to 0.05 MPa to ensure that the essential oil can fully penetrate into the polylactic acid matrix.
[0027] Preferably, the step of ultrasonic treatment in step 3 is to treat the mixture at a frequency of 20 kHz for at least 30 minutes to ensure uniform dispersion of the nanoparticles and prevent agglomeration.
[0028] The present invention provides an electronic cigarette flavor sheet based on high-efficiency, environmentally friendly, low-temperature high-molecular volatilization and a production process thereof.
[0029] It has the following beneficial effects:
[0030] 1. The present invention significantly improves the thermal conductivity of the composite material by introducing aluminum oxide nanoparticles into the polylactic acid matrix and optimizing the thermal conductivity of the material using the Maxwell model. Compared with pure polylactic acid material, the thermal conductivity is increased by about 3 times, so that the essential oil can volatilize evenly when heated at low temperature, avoiding the problem of local overheating or uneven volatilization of the essence caused by poor heat conduction in traditional essence tablets.
[0031] 2. The present invention optimizes the ratio of essential oil and the compatibility of the polylactic acid matrix, and ensures that the essential oil can be released evenly at a stable and continuous rate when heated. The Flory-Huggins theory is used to calculate the optimal ratio of essential oil to matrix, so that the essential oil can be effectively volatilized under low temperature conditions, while extending the service life of the essence sheet and improving the user experience.
[0032] 3. The present invention introduces a microporous structure, which significantly improves the diffusion rate of essential oils. The microporous structure generated by the controllable foaming technology shortens the diffusion path of the essential oils and improves the volatilization efficiency. At the same time, the micropores increase the specific surface area of the essential oils, making the fragrance release more lasting and uniform, thereby significantly improving the user experience of electronic cigarettes.
[0033] 4. The comprehensive optimization technology of the present invention ensures the stability of the flavor tablets during use and the uniform release of the essential oils, so that electronic cigarette users can obtain a more lasting and uniform fragrance experience. Compared with traditional flavor tablets, the product of the present invention has more stable volatilization, will not produce odor or excessive volatilization due to overheating, and significantly improves the overall experience of users. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The present invention is a flow chart of the method. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Embodiment 1:
[0037] Please refer to the attached Figure 1 The embodiment of the present invention provides an electronic cigarette flavor sheet based on high-efficiency, environmentally friendly, low-temperature polymer volatilization, and the flavor sheet includes:
[0038] The flavor sheet includes a composite material based on polylactic acid, wherein the modification of the polylactic acid includes compounding with aluminum oxide nanoparticles to improve its thermal stability;
[0039] The composite material further includes a certain proportion of essential oil, which is bonded to the polylactic acid through a specific chemical bond for volatilization at a controlled rate and low temperature during heating;
[0040] The volume fraction of aluminum oxide nanoparticles is precisely controlled at 5%, which enhances the thermal conductivity of the composite material and achieves a more uniform heat distribution, thereby optimizing the volatilization performance of the flavor;
[0041] The thermal conductivity of the composites was calculated based on a modified Maxwell model that takes into account the shape and distribution heterogeneity of the nanoparticles.
[0042] In one embodiment, step 1.1: selection of a matrix material of polylactic acid
[0043] In this embodiment, polylactic acid is selected as the matrix material. Polylactic acid is a high molecular polymer widely used in environmentally friendly materials, with good biodegradability, thermal stability and mechanical strength. Since the focus of the present invention is to achieve the volatilization of flavors under low temperature conditions, the selection of polylactic acid as the matrix material can ensure that the material has good heat resistance and structural integrity during use. At the same time, the degradability of polylactic acid meets environmental protection requirements and can reduce the environmental burden of the product after use. The molecular weight of polylactic acid is selected to be 200,000, which can ensure the processing performance strength of the material.
[0044] Step 1.2: Selection and modification of alumina nanoparticles
[0045] In this embodiment, aluminum oxide nanoparticles are selected as fillers to improve the thermal conductivity of the polylactic acid matrix. Aluminum oxide nanoparticles are an ideal thermal conductivity enhancing material due to their high thermal conductivity and good chemical stability. However, untreated aluminum oxide nanoparticles are easily agglomerated in the polylactic acid matrix, thereby affecting thermal conductivity and mechanical properties. In order to improve the dispersibility of nanoparticles and compatibility with the polylactic acid matrix, aluminum oxide nanoparticles are silanized in this embodiment.
[0046] During the silanization process, the aluminum oxide nanoparticles were immersed in an ethanol solution of a silane coupling agent solution (3-aminopropyltriethoxysilane), stirred for 3 hours, and then centrifuged and washed to remove unreacted silane. The modified aluminum oxide nanoparticles have better surface affinity and dispersibility, and can be evenly distributed in the polylactic acid matrix, thereby improving the thermal conductivity of the entire composite material.
[0047] 2. Selection and proportion optimization of essential oils
[0048] Step 2.1: Selection and proportion calculation of essential oils
[0049] In this embodiment, citrus and mint essential oils are selected as the main flavor ingredients. These essential oils have a high boiling point and chemical stability, and can continuously release fragrance at low temperatures without affecting the user experience of electronic cigarettes. In order to ensure the uniform distribution and stable volatilization of the essential oils in the polylactic acid matrix, this embodiment uses the Flory-Huggins theory to optimize the compatibility of the essential oils with polylactic acid. By calculating the interaction parameters between the essential oils and polylactic acid, the optimal addition ratio of the essential oils can be determined.
[0050] According to Flory-Huggins theory, the volume ratio of essential oil and polylactic acid is set at 2%. This ratio is optimized by calculating the molar volume of essential oil and the solubility parameter of polylactic acid. The closer the solubility parameter is, the better the compatibility between materials. The solubility difference between the essential oil and polylactic acid in the present embodiment is less, which ensures that the essential oil can be evenly dispersed and effectively volatilized in the polylactic acid matrix.
[0051] 3. Preparation process
[0052] Step 3.1: Mixing and ultrasonic dispersion
[0053] In this embodiment, polylactic acid is first mixed with modified aluminum oxide nanoparticles. In order to ensure uniform dispersion of aluminum oxide nanoparticles in the polylactic acid matrix, an ultrasonic dispersion device is used for treatment. The specific steps are: at a temperature of 50°C, polylactic acid is mixed with 5% volume fraction of aluminum oxide nanoparticles, and essential oil is gradually added at a volume ratio of 2%. Then, the mixture is treated with an ultrasonic device at a frequency of 20kHz for 30 minutes.
[0054] The role of ultrasonic dispersion is to break the agglomeration of nanoparticles through sound wave vibration, so that they are evenly distributed in the polylactic acid matrix. The time and frequency of ultrasonic treatment are determined through experimental optimization, which can effectively improve the dispersion efficiency without destroying the structure and performance of the material.
[0055] Step 3.2: Hot Pressing
[0056] In this embodiment, the mixed material is placed in a mold for hot pressing. The hot pressing conditions are 65°C, 200psi pressure, and the pressing time is 10 minutes. The selection of this process condition is based on the optimization of the thermal stability and mechanical properties of the material, which can ensure that the material has sufficient strength when heated at low temperature, and the volatility of the essential oil will not be affected by excessive heating. The thickness of the flavor sheet after hot pressing is controlled at 1 mm to ensure that the essential oil can be evenly released when using the electronic cigarette device.
[0057] Step 3.3: Cooling and cutting
[0058] In this embodiment, the hot-pressed flavor sheet is naturally cooled at room temperature for 2 hours to ensure that the mechanical properties of the material are stable. The cooling process is crucial to the structural stability of the material, because too fast cooling may cause stress inside the material. After cooling, the flavor sheet is cut into small pieces according to the specifications of 2cm x 2cm to meet the use requirements of the electronic cigarette device. The size optimization of the cutting is determined based on experiments, which can ensure that the amount of flavor and the volatilization effect used each time are consistent.
[0059] 4. Performance Testing
[0060] Step 4.1: Thermal conductivity test
[0061] In this embodiment, the thermal conductivity of the flavor sheet was measured by the laser flash method. The results show that the thermal conductivity of the polylactic acid matrix material containing 5% alumina nanoparticles increased from 0.35W / mK to 1.05W / mK, which is about 3 times that of pure polylactic acid material. This result shows that by introducing alumina nanoparticles, the thermal conductivity of the flavor sheet has been significantly improved, and it can conduct heat more evenly, thereby achieving a more stable flavor volatilization effect.
[0062] Step 4.2: Flavor release rate test
[0063] In this embodiment, a special volatility test device is used to measure the release rate of essential oil of the flavor tablet. The test shows that when the flavor tablet is heated to 40°C, it can stably release the essential oil, and its volatilization rate is 25% higher than that of the traditional flavor tablet. In addition, the volatilization process of the flavor tablet is more uniform, avoiding the excessive volatilization phenomenon caused by local overheating of the traditional flavor tablet.
[0064] The essential oil is selected from the category of essential oils with a higher boiling point and a stable chemical structure to ensure effective volatilization even at low temperatures.
[0065] The optimization of thermal conductivity of composite materials is based on the Maxwell model. The model formula is shown below, which is used to accurately control the dispersion uniformity and shape factor of nanoparticles:
[0066]
[0067] where k matrix is the thermal conductivity of polylactic acid, k particle is the thermal conductivity of alumina, and φ is the volume fraction of alumina nanoparticles.
[0068] The essential oil is selected from citrus or mint, and the volume ratio of the essential oil to the polylactic acid is 2%, which is optimized based on the Flory-Huggins theory to achieve the best volatilization effect and fragrance persistence, calculated using the following formula:
[0069]
[0070] Where V 1 is the molar volume of the essential oil, R is the gas constant, T is the absolute temperature, δ 1 and δ 2 are the solubility parameters of essential oils and polylactic acid, respectively.
[0071] Embodiment 2:
[0072] This embodiment provides a process for producing electronic cigarette flavor tablets based on high-efficiency, environmentally friendly, low-temperature high-molecular-weight volatilization, based on the above embodiment, including the following steps:
[0073] Step 1, mixing the modified polylactic acid and alumina nanoparticles in a predetermined ratio to ensure that the alumina nanoparticles are evenly distributed;
[0074] Step 2, adding the essential oil to the mixture, controlling the adding speed and mixing temperature to maintain the chemical stability of the essential oil;
[0075] Step 3: Using ultrasonic technology to optimize the dispersion of aluminum oxide nanoparticles in the polylactic acid matrix, thereby improving the thermal conductivity and flavor release performance of the final product;
[0076] Step 4: Form the flavor tablets by hot pressing under controlled pressure and temperature to ensure the thermal stability of the material and the uniform volatilization of the flavor.
[0077] In step 2, in the step of mixing modified polylactic acid and aluminum oxide nanoparticles, dynamic light scattering technology is used to accurately measure and monitor the average particle size and particle size distribution of the nanoparticles to ensure that the average particle size of the nanoparticles is controlled within the range of 50 to 100 nanometers to achieve a predetermined dispersion uniformity.
[0078] In step 2, in the step of adding essential oil, an automatic titration system is used to accurately control the amount of essential oil added. The system automatically adjusts the addition rate of the essential oil based on the Flory-Huggins theory and real-time solubility monitoring results to ensure that the volume ratio of essential oil to polylactic acid is maintained at a constant 2%.
[0079] In step 4, the hot pressing molding process is carried out in a specific device that can accurately control the pressure and temperature. The pressure is set to 200 psi, the temperature is set to 65°C, and the pressing time is fixed to 10 minutes. During the melt blending process in step 1, a high-speed agitator is used to improve the dispersion uniformity of the nanoparticles to ensure that the flavor sheet has good thermal conductivity.
[0080] In step 2, the pressure range of the vacuum extraction process is controlled within 0.01 to 0.05 MPa to ensure that the essential oil can fully penetrate into the polylactic acid matrix.
[0081] Step 3: Ultrasonic treatment is performed on the mixture at a frequency of 20 kHz for at least 30 minutes to ensure uniform dispersion of the nanoparticles and prevent agglomeration.
[0082] Comparative Example 1:
[0083] Preferred embodiment 1: adding different nanofillers in combination
[0084] Implementation content:
[0085] In this preferred embodiment, in addition to using aluminum oxide nanoparticles, graphene nanosheets with excellent thermal conductivity are further introduced as a second thermal conductive filler to form a multi-component nanofiller composite material. Graphene nanosheets have extremely high thermal conductivity and good mechanical strength, which can further improve the thermal conductivity of the polylactic acid matrix. The specific ratio is: the volume fraction of aluminum oxide nanoparticles is 3%, and the volume fraction of graphene nanosheets is 2%.
[0086] In this embodiment, the graphene nanosheets used have a thickness of 1-5 nanometers and a diameter of 5-10 micrometers, which can work well with the aluminum oxide nanoparticles to improve the thermal conductivity. The mixed filler is evenly distributed in the polylactic acid matrix by ultrasonic dispersion.
[0087] The Maxwell-Garnett model is used to calculate the thermal conductivity of this dual-filler composite material. The model can take into account the distribution and shape parameters of the multiphase fillers and optimize the thermal conductivity.
[0088] Through the synergistic effect of alumina and graphene nanosheets, the thermal conductivity of the composite material is further improved, and the thermal conductivity coefficient can be increased to 1.2W / mK. Compared with composite materials using only alumina, the combination of multiple nanofillers can more effectively improve the heat transfer path and further improve the uniform volatilization effect of the flavor. This preferred embodiment can improve the volatilization efficiency of the flavor sheet under low temperature conditions, while further improving the mechanical strength of the polylactic acid matrix and extending the service life of the product.
[0089] Comparative Example 2: Preferred Example 2: Introduction of Microporous Structure
[0090] Implementation content:
[0091] In this preferred embodiment, a microporous structure is introduced into the polylactic acid matrix by using a controllable foaming technology to improve the diffusion and volatilization efficiency of the essential oil. The specific steps are: after the polylactic acid matrix is mixed with aluminum oxide nanoparticles and essential oil, a foaming agent is introduced into the material, and a uniformly distributed microporous structure is formed by controlling the temperature and pressure during the hot pressing process, and the pore size is controlled within the range of 10-50 microns.
[0092] In this embodiment, the amount of foaming agent used is controlled between 1% and 3%, ensuring that a microporous structure is generated without affecting the mechanical properties of the substrate. By controlling the temperature and pressure of the foaming process, a uniform microporous distribution is formed, while preventing the pores from being too large to affect the strength of the flavor tablet.
[0093] The diffusion rate of essential oils is optimized using Fick's diffusion law. The microporous structure can increase the surface area of the essential oils, thereby increasing the volatilization rate. Fick's law is as follows:
[0094]
[0095] Among them, J is the diffusion flux, D is the diffusion coefficient, ΔC is the concentration gradient, and Δx is the diffusion path length. By introducing the microporous structure, the diffusion path length of the essential oil is shortened, thereby accelerating the volatilization process.
[0096] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. Based on high-efficiency, environmentally friendly, low-temperature polymer volatile electronic cigarette flavor tablets, characterized in that: The flavor tablets include: The flavor sheet includes a composite material based on polylactic acid, wherein the modification of the polylactic acid includes compounding with aluminum oxide nanoparticles to improve its thermal stability; The composite material further includes a certain proportion of essential oil, which is bonded to the polylactic acid through a specific chemical bond and is used to volatilize at a controlled rate and low temperature during heating; The volume fraction of aluminum oxide nanoparticles is precisely controlled at 5%, which enhances the thermal conductivity of the composite material and achieves a more uniform heat distribution, thereby optimizing the volatilization performance of the flavor; The thermal conductivity of the composite material is calculated according to the improved Maxwell model, which takes into account the shape and distribution heterogeneity of the nanoparticles.
2. The high-efficiency, environmentally friendly, low-temperature high-molecular-weight volatilization electronic cigarette flavor sheet according to claim 1 is characterized in that: The essential oil is selected from the category of essential oils with a relatively high boiling point and a stable chemical structure to ensure effective volatilization even at low temperatures.
3. The high-efficiency, environmentally friendly, low-temperature high-molecular-weight volatilization electronic cigarette flavor sheet according to claim 1 is characterized in that: The thermal conductivity optimization of the composite material is based on the Maxwell model, and the model formula is as follows, which is used to accurately control the dispersion uniformity and shape factor of the nanoparticles: where k matrix is the thermal conductivity of polylactic acid, k particle is the thermal conductivity of alumina, and φ is the volume fraction of alumina nanoparticles.
4. The high-efficiency, environmentally friendly, low-temperature high-molecular-weight volatilization electronic cigarette flavor sheet according to claim 1 is characterized in that: The essential oil is selected from citrus or mint, and the volume ratio of the essential oil to polylactic acid is 2%, which is optimized based on the Flory-Huggins theory to achieve the best volatilization effect and fragrance persistence, and is calculated using the following formula: Where V1 is the molar volume of the essential oil, R is the gas constant, T is the absolute temperature, and δ1 and δ2 are the solubility parameters of the essential oil and polylactic acid, respectively.
5. A process for producing an efficient, environmentally friendly, low-temperature high-molecular-weight volatile electronic cigarette flavor tablet, according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1, mixing the modified polylactic acid and alumina nanoparticles in a predetermined ratio to ensure that the alumina nanoparticles are evenly distributed; Step 2, adding the essential oil to the mixture, controlling the adding speed and mixing temperature to maintain the chemical stability of the essential oil; Step 3: Using ultrasonic technology to optimize the dispersion of aluminum oxide nanoparticles in the polylactic acid matrix, thereby improving the thermal conductivity and flavor release performance of the final product; Step 4: Form the flavor tablets by hot pressing under controlled pressure and temperature to ensure the thermal stability of the material and the uniform volatilization of the flavor.
6. The process for producing electronic cigarette flavor tablets based on high-efficiency, environmentally friendly, low-temperature high-molecular-weight volatilization according to claim 5 is characterized in that: In step 2, in the step of mixing modified polylactic acid and aluminum oxide nanoparticles, dynamic light scattering technology is used to accurately measure and monitor the average particle size and particle size distribution of the nanoparticles to ensure that the average particle size of the nanoparticles is controlled within the range of 50 to 100 nanometers to achieve a predetermined dispersion uniformity.
7. The process for producing electronic cigarette flavor tablets based on high-efficiency, environmentally friendly, low-temperature high-molecular-weight volatilization according to claim 5 is characterized in that: In the step 2, in the step of adding essential oil, an automatic titration system is used to accurately control the amount of essential oil added. The system automatically adjusts the addition rate of the essential oil based on the Flory-Huggins theory and real-time solubility monitoring results to ensure that the volume ratio of essential oil to polylactic acid is maintained at a constant 2%.
8. The process for producing electronic cigarette flavor tablets based on high-efficiency, environmentally friendly, low-temperature high-molecular-weight volatilization according to claim 5 is characterized in that: In the step 4, the hot pressing molding process is carried out in a specific device that can accurately control the pressure and temperature. The pressure is set to 200 psi, the temperature is set to 65°C, and the pressing time is fixed to 10 minutes. During the melt blending process in the step 1, a high-speed agitator is used to improve the dispersion uniformity of the nanoparticles to ensure that the flavor tablet has good thermal conductivity.
9. The process for producing electronic cigarette flavor tablets based on high-efficiency, environmentally friendly, low-temperature high-molecular volatilization according to claim 5 is characterized in that: In the step 2, the pressure range of the vacuum extraction process is controlled within a range of 0.01 to 0.05 MPa to ensure that the essential oil can fully penetrate into the polylactic acid matrix.
10. The process for producing electronic cigarette flavor tablets based on high-efficiency, environmentally friendly, low-temperature high-molecular-weight volatilization according to claim 5 is characterized in that: The step of ultrasonic treatment in step 3 is to treat the mixture at a frequency of 20 kHz for at least 30 minutes to ensure uniform dispersion of the nanoparticles and prevent agglomeration.